2018
DOI: 10.1371/journal.pone.0199135
|View full text |Cite|
|
Sign up to set email alerts
|

A sialoadenectomy is associated with an increased risk of coronary heart disease: A three-year follow-up study

Abstract: Little is known regarding the long-term adverse effects of a sialoadenectomy. The purpose of this study was to estimate the risk of coronary heart disease (CHD) among patients receiving a sialoadenectomy procedure by utilizing a cohort study based on a population-based database in Taiwan. This study retrieved data of the study sample from the Longitudinal Health Insurance Database 2005. This retrospective cohort study included 608 patients who underwent a sialoadenectomy and 1824 propensity score-matched compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The WHO study found that the incidence of coronary heart disease (CHD) is the highest among cardiovascular diseases [1,2]. The famous GRACE study shows that although the drug and interventional therapy of CHD have achieved great progress and achieved good results [3].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO study found that the incidence of coronary heart disease (CHD) is the highest among cardiovascular diseases [1,2]. The famous GRACE study shows that although the drug and interventional therapy of CHD have achieved great progress and achieved good results [3].…”
Section: Introductionmentioning
confidence: 99%